(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
The research shows the role of the participatory leadership style in enhancing organizational loyalty through positive psychological capital as a mediating variable. In order to achieve this, the research questions centered on the nature of the correlation and influence relationships between the research variables. For this reason, the research relied on the dimensions of each variable separately to demonstrate the role of participatory leadership in improving And reaching the best solutions and decisions for the employees of the organization by taking into account the opinions of the employees, freedom of expression, and their sense of responsibility in order to achieve the required level, which creates confidence among the employees and gives them their importance at work, which leads to the availability of a positive psychological climate for the employees that makes the work environment more lively and positive and reduces stress. The work enhances the employees’ adherence to the organization under study and enhances their organizational loyalty. The General Secretariat of the Abbasid Holy Shrine was chosen to test the research hypotheses. The researcher used the questionnaire as a research tool and a means of obtaining data. He conducted some interviews for clarification and clarification. The research relied on the descriptive analytical approach. The research community was represented by workers in the secretariat. The general survey of the Holy Abbasid Shrine, and the research sample amounted to (425) respondents. (403) questionnaires were retrieved valid for statistical analysis and through the statistical package for the (Spss V.26) The General Assembly of the Holy Abbasid Shrine is concerned with applying the participatory leadership style, through which a participatory organizational climate is created in which all meanings of cooperation, morale, social spirit, and collective responsibility are embodied in the work relationship between employees and management, which would create a stable work environment free of organizational problems and disagreements, which... It leads to enhancing levels of organizational loyalty, and there is an indirect effect of positive psychological capital if it mediates between participatory leadership style and organizational loyalty, which indicates that the research sample’s connection to the workplace is a religious-ideological, psychological, and spiritual connection, before it is primarily a professional commitment. Therefore, we find the research sample harnessing all its capabilities and energies to promote and raise the style of participatory leadership to ensure the strengthening of organizational loyalty for workers in the General Secretariat of the Abbasid Shrine.